Spiritual values and ecosystem services of sacred groves in Karnataka, India - Ormsby, Alison A.; Krishnan, Smitha (Routledge, 2022)
Sacred groves are community-conserved forests that are protected for cultural reasons. Many also serve a biological conservation value because they harbour a high diversity of species and provide ecosystem services such as watershed values, carbon sequestration, pollination, and seed banks. India has an estimated 100,000 sacred groves. Research conducted in South India found that residents near sacred groves recognized and valued the ecosystem services provided by the groves, in addition to the spiritual values for which the groves are primarily conserved. Although currently many groves are not legally recognized as protected areas, in the future, it is important that the groves continue to be supported for their intangible cultural and spiritual values. In addition, the role that community grove managers play in forest conservation should be recognized and affirmed. While some larger sacred groves may be targeted to be part of a payment for ecosystem services programme, it is advised that these economic arrangements are entered with caution to avoid disrupting the cultural and spiritual values, and local management, of the groves.